Bank Himbara's Employee Organizational Performance Model Through Employee Competencies - Manalu, Brilliant Handyman; Maria, Elvie; Ady, Sri Utami; Sayidah, Nur (Ann Publisher, 2025)
Digital banking has become an integral part of the modern banking industry, especially for the State-Owned Bank Association (Himbara). This transformation significantly affects operations and organizational structures, including workforce restructuring, where many employees are transferred to sales units with higher targets. However, this placement poses a challenge when most employees do not have the appropriate competencies for their new roles. This study explores the role of Strategic Human Resource Management (SHRM) and workforce restructuring in improving employee performance through adjusting their competencies. This study uses a quantitative descriptive method, with data collected through a survey of 205 permanent employees of Bank Himbara in the North Sumatra region, selected using the Slovin formula. This study uses regression analysis to test the relationship between these variables. The results show that the right SHRM can improve employee performance, but this success depends on employee competencies following the demands of their new roles. Restructuring that is not balanced with competency development causes a decrease in productivity. These findings provide important insights for HR managers in designing effective policies in the digital banking era.